Academic Performance of Left-Behind Senior High School Students in the Philippines: Impacts of Parental Migration - Martina Chloe Mari Apolinario; Inero Ancho; Rufo Gil Albor; Nephtaly Joel Botor; Daisy Pelegrina; Phrygian Almeda (ASEAN Journal of Educational Research and Technology, 2025)
The migration of Filipino workers overseas remains a major socio-economic phenomenon, offering financial stability yet creating emotional and academic challenges for left-behind children. This qualitative phenomenological study examined how parental absence affects the academic performance of senior high school students in Los Baños, Laguna, whose parents work abroad. Data were gathered through semi-structured interviews with purposively selected Grade 12 students meeting specific criteria. Thematic analysis revealed three key themes: thriving amidst loneliness, flourishing academic independence, and repaying sacrifices through excellence. While remittances eased financial burdens, students reported feelings of isolation, lack of parental guidance, and academic pressure driven by the desire to honor their parents’ sacrifices. Strong communication and adaptive coping strategies emerged as vital in mitigating adverse effects. The study underscores the need for school-based support systems and policy interventions addressing the psychosocial well-being and academic needs of left-behind students.